Mentoring support Sustaining Technical Education - Aprajita Singh (Journal of Advanced Research in Public Policy and Administration, 2021)
In recent past India has witnessed a number of reforms in education sector. However, these changes have affected the supply and demand and education quality. Higher quality, lower cost of production and good service are the emerging needs of customers today [18]. This is a matter of great concern that students are not meeting the standards of industries. Hence it is very much necessary that the students which are coming out from technical institutions must be directly useful for industries. In order to meet this requirement of imparting high quality technical education one must maximize the effectiveness of the institution and in order to improve the effectiveness of any institution the various factors affecting it are identified and analyzed. [16]NAAC annual reports of previous four years indicate decline in the enrollment in technical education like Engineering and in many institutions number of seats just remain vacant. The quality of students enrolling in technical education are not very technical and academically sound today. Individual attention is required and learning at an individuals’ pace is needed. Students require specific and special attention hence students mentoring plays an important role in learning of the students. A Student has to be understood at an individual level and the learning has to be very specific. Student has to be made comfortable at whatever basic concepts knowledge that he/she possesses. Institutions have to invest more time and resources to cater to students entering Technical Education today. For Institutions to sustain it is advisable to improve the process of individual student mentoring by faculty members. The purpose of the study is to determine if graduate students are impacted by mentoring. The researcher seeks to determine if mentoring increases students’ test scores .With this purpose in mind past data of 421 students was studied which comprise of students in technical education over four years. The aim of this study is to determine factors like student support as far as mentoring is concerned which impacts student’s retention affecting the sustainability of educational institution. This is an exploratory study that collected data and analyses done to study impact of mentoring program in student retention Research results also indicated that impact of mentoring on improving the test scores is not that significant but it does impact student retention.